The Life and Death of a Metaphor, or the Metaphysics of Metaphor - Josef Stern (Baltic International Yearbook of Cognition, Logic and Communication, 2007)
This paper addresses two issues: (1) what it is for a metaphor to be either alive or dead and (2) what a metaphor must be in order to be either alive or dead. Both issues, in turn, bear on the contemporary debate whether metaphor is a pragmatic or semantic phenomenon and on the dispute between Contextualists and Literalists. In the first part of the paper, I survey examples of what I take to be live metaphors and dead metaphors in order to establish that there is a phenomenon here to be explained. I then propose an explanation of metaphorical vitality (and by implication of metaphorical death) in terms of the dependence of the interpretation of a metaphor on a family or network of expressions specific to its context of utterance. I then argue that only a Literalist account of metaphor — one that posits metaphorical expressions (a la Stern (2000))—and not Contextualist and Gricean approaches can accommodate this explanation. Finally, I discuss some objections to my Literalist account and sketch an explanation of types to counter Platonistic objections to my metaphorical expression types.
Keywords: philosophy; linguistic